The Role of Fiqh Teachers in Implementing Project-Based Learning Within the Merdeka Curriculum at Madrasah Tsanawiyah - Tiara, Meza; Marinda, Aflia Bela; Wanto, Deri; Idris, Muhammad; Kristina, Epa (INCARE, International Journal of Educational Resources, 2025)
This study examines the role of Fiqh teachers in the implementation of Project-Based Learning (PjBL) within the context of the Merdeka Curriculum at MTs N 1 Lebong. This curriculum aims to improve the quality of education by integrating character education and the development of student competencies. The objective of this study is to analyze the teacher's role in designing, implementing, and evaluating PjBL, as well as the challenges encountered during the process. The methods used include in-depth interviews with teachers, classroom observations, and analysis of students' project documentation. The findings indicate that the teacher's role is crucial in guiding students to understand Fiqh material through contextual projects, although they face challenges such as limited facilities and the readiness of both students and teachers. In addition, this study highlights the importance of teacher training to enhance the effective implementation of PjBL in Fiqh subjects.